A descriptive study of frequency of short term complications in late preterm neonates at a tertiary care hospital Rawalpindi - Ijaz, Sadaf; Shamsher, Maria; Ismail, Ismat; Ayub, Aqeela (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the frequency of short-term complications in late preterm neonates in a tertiary care setting. Method: The observational study was conducted at Benazir Bhutto Hospital, Rawalpindi, Pakistan, from December 1, 2020, to May 31, 2021, and comprised late preterm neonates. Frequency of complications were noted in the subjects. Data was analysed using SPSS 22. Results: Of the 200 subjects, 108(54%) were males, 84(42%) were aged 34-35 weeks. Among the complications, sepsis was the most frequent 88(44%), followed by respiratory distress syndrome RDS 58(29%). Mean weight was 2kg with standard deviation of 0.42 and mean day of life at presentation was day 2 with standard deviation of 1.9. Most common maternal risk factor was premature rupture of membrane 48(24%). Conclusion: Late preterm neonates had critical complications. The health authorities should formulate policies in this regard. Key Words: Late preterm, Short-term complications, RDS, Neonatal sepsis.